The Effect of Nigella sative Extract on the Fungi that Isolated from Desktop's of the Tables (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The study  included the isolation and diagnosis of the fungi from the Desktop's of the tables  (instructers ,medical laboratories). The study appeared many of the different kinds of fungi:(Absidia sp,Candidia sp, Aspergillus  sp,Penicillum  sp and Alternaria sp)The  rate of appearance of the type of the fungi  in Desktop's of the tables instructers   is the higher than the Desktop's of the tables of the medical laboratories .The rate of appearance of the fungi   Candidia is recoded 36.8% and Penicillum sp,Aspergillus niger  is recoded 21.05% and Aspergillus flavus recoded 5.2 %, Abisidia sp recoded  15.7%. While  in the Desktop's of the tables medical laboratories  the fungi Aspergillus  terrus is recorded 15.7% and the fungi  Absidia ,Candidia, Apergillus niger is recoded 20% , Penicillum sp ,Alternaria sp is recoded  10%. The study  showed  the influence  of the hot   water  extract  of   the Nigella sative the concentration which is used(10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the  fungi Penicillum sp in the concentration (30,40) mg/ml and  the  range of the diameter colony of the yeast Candidia  albicanis in the concentration 30 mg/ml the (1)cm. While the fungi Aspergillus  niger in the concentration (10,20)mg/ml is given resistance toward the extract 2.